Do Voters Prefer Women Judges? Deconstructing the Competitive Advantage in State Supreme Court Elections. (December 2019) - Gill, Rebecca D.; Eugenis, Kate
Abstract : Although many people believe that women are disadvantaged by the electoral process, recent research shows women generally do at least as well as men when they run for office. We investigate the gender dynamics of state supreme court elections. We find evidence that women do enjoy an electoral advantage when they run for judicial office. However, unlike previous work, we find that this advantage is highly contingent on the electoral context. Using an original dataset of competitive judicial elections from 1998 to 2014, we find that women only have a significant vote share advantage when they run as a challenger against a sitting incumbent. The advantage does not apply to women as incumbents or in open seat elections. These findings raise important questions about the interplay of institutional barriers and election aversion for the advancement of women in electoral judicial politics.